Seroprevalence of West Nile Virus in Wild Birds in Far Eastern Russia Using a Focus Reduction Neutralization Test - Murata, Ryo (The American Society of Tropical Medicine and Hygiene, 2011)
West Nile (WN) virus has been spreading geographically to non-endemic areas in various parts of the world. However, little is known about the extent of WN virus infection in Russia. Japanese encephalitis (JE) virus, which is closely related to WN virus, is prevalent throughout East Asia. We evaluated the effectiveness of a focus reduction neutralization test in young chicks inoculated with JE and WN viruses, and conducted a survey of WN infection among wild birds in Far Eastern Russia. Following single virus infection, only neutralizing antibodies specific to the homologous virus were detected in chicks. The neutralization test was then applied to serum samples from 145 wild birds for WN and JE virus. Twenty-one samples were positive for neutralizing antibodies to WN. These results suggest that WN virus is prevalent among wild birds in the Far Eastern region of Russia.